(untitled) - Moore, John (New York, 1996)
Colloquial Vietnamese is easy to use and completely up-to-date, with no prior knowledge of the language required. These CDs are recorded by native Vietnamese speakers and will play on any audio system. The material can be used on its own or to accompany the book, helping you with pronunciation and listening skills.
Keywords: Vietnamese language,Vietnamese language,Vietnamese language; Conversation and phrase books,English,Spoken vietnamese,Pronunciation